Transcriptomic analysis reveals Toxoplasma gondii strain-specific differences in host cell response to dense granule protein GRA15 - Liu, Qing; Gao, Wen-Wei; Elsheikha, Hany M.; He, Jun-Jun; Li, Fa-Cai; Yang, Wen-Bin; Zhu, Xing-Quan (Springer, 2018)
Growth and replication of the protozoan parasite Toxoplasma gondii within host cell entail the production of several effector proteins, which the parasite exploits for counteracting the host’s immune response. Despite considerable research to define the host signaling pathways manipulated by T. gondii and their effectors, there has been limited progress into understanding how individual members of the dense granule proteins (GRAs) modulate gene expression within host cells. The aim of this study was to evaluate whether T. gondii GRA15 protein plays any role in regulating host gene expression. Baby Hamster Kidney cells (BHK-21) were transfected with plasmids encoding GRA15 genes of either type I GT1 strain (GRA15I) or type II PRU strain (GRA15II). Gene expression patterns of transfected and nontransfected BHK-21 cells were investigated using RNA-sequencing analysis. GRA15I and GRA15II induced both known and novel transcriptional changes in the transfected BHK-21 cells compared with nontransfected cells. Pathway analysis revealed that GRA15II was mainly involved in the regulation of Tumor Necrosis Factor (TNF), NF-κB, HTLV-I infection and NOD-like receptor signaling pathways. GRA15I preferentially influenced the synthesis of unsaturated fatty acids in host cells. Our findings support the hypothesis that certain functions of GRA15 protein are strain-dependent; and that GRA15 modulates the expression of signaling pathways and genes with important roles in T. gondii pathophysiology. A greater understanding of host signaling pathways influenced by T. gondii effectors, would allow the development of more efficient anti-T. gondii therapeutic schemes, capitalizing on disrupting parasite virulence factors to advance the treatment of toxoplasmosis.